FACTORS AFFECTING LIBRARY ANXIETY OF GRADUATE SCHOOL STUDENTS IN GADJAH MADA UNIVERSITY - Noprianto, Eko (D3 Teknisi Perpustakaan Fakultas Vokasi Universitas Airlangga, 2019)
Background of Study: The library has an important role in supporting the process of education and research in a university. Students need a library as a place to study, discuss, work on assignments, or do research. But sometimes students who visit the library feel uncomfortable and confused about the condition they are facing that is usually known as library anxiety.Purpose: This study aims at identifying library anxiety among Graduate School Students in Gadjah Mada University, and examine several factors considered to affect library anxiety, namely barriers to service by librarians, affective, library comfort, knowledge of the library, mechanical/technological, information retrieval, regulation, resources.Method: This is aquantitative deductive research, using a survey approach. The population were Graduate School Students at Gadjah Mada University, with a total sample of 60 students taken by purposive sampling technique. Data were collected using questionnaires. The data were analyzed using smartPLS 3.0.Finding: The results showed that 95% of Graduate School students at Gadjah Mada University experienced library anxiety. There are 8 factors that affecting library anxiety of Graduate School Students in Gadjah Mada University, namely barriers to service by librarians, affective, library comfort, knowledge of the library, mechanic/technology, information retrieval, regulation, resources.Conclution: The library anxiety experienced by Graduate School students in Gadjah Mada University is 100% influenced by those 8 factors tested in this study.